Peran Guru Pendidikan Pancasila dalam Pencegahan Tindakan Bullying di MTS Al-Mursyidiyyah Pamulang Kota Tangerang Selatan - Sari, Ratna; Wahidin, Darto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Bullying remains a serious issue in schools, with significant impacts on students’ psychological, social, and academic development. Previous studies have mostly focused on the role of guidance and counseling teachers, while the contribution of Pancasila Education teachers in bullying prevention has received limited scholarly attention. This study aims to analyze the role of Pancasila Education teachers in preventing bullying at MTs Al-Mursyidiyyah Pamulang. Using a qualitative case study design as outlined by Yin, data were collected through interviews, observations, and document analysis involving Pancasila Education teachers, school staff, and seventh-grade students. Data were analyzed using Miles and Huberman’s interactive model with triangulation to ensure validity. The findings reveal that Pancasila Education teachers play a central role in fostering students’ character by embedding Pancasila values, modeling positive behavior, and directly intervening in bullying cases. These efforts align with Olweus’ theory of bullying prevention and contribute to creating a safe, inclusive, and supportive school climate. The study underscores the importance of integrating Pancasila values with comprehensive anti-bullying strategies, thereby enriching existing literature and offering practical insights for schools to strengthen preventive measures against bullying.